2014
DOI: 10.1159/000366055
|View full text |Cite
|
Sign up to set email alerts
|

Bilberry-Derived Anthocyanins Prevent IFN-γ-Induced Pro-Inflammatory Signalling and Cytokine Secretion in Human THP-1 Monocytic Cells

Abstract: Background/Aims: Anthocyanins are plant-derived dietary components that are highly abundant, for example, in bilberries. We have previously demonstrated that anthocyanins exert anti-inflammatory properties in mouse colitis models and ameliorate disease activity in ulcerative colitis patients. Here, we studied the molecular mechanisms through which anthocyanin-containing bilberry extract (BE) exerts anti-inflammatory effects in human monocytic THP-1 cells. Methods: THP-1 cells were pre-incubated with BE 20 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…In human monocytic THP-1 cells, bilberry extract reduced interferon-γ (IFN-γ)-induced signal protein activation, pro-inflammatory gene expression and cytokine secretion, and enhanced tumor necrosis factor-α (TNF-α)-induced responses [28] . Even a recent study on biopsy samples of patients with ulcerative colitis treated with an oral anthocyanin-rich bilberry preparation during an open label clinical trial revealed reduced amounts of the proinflammatory cytokines IFN-γ and TNF-α [29] .…”
Section: Discussionmentioning
confidence: 99%
“…In human monocytic THP-1 cells, bilberry extract reduced interferon-γ (IFN-γ)-induced signal protein activation, pro-inflammatory gene expression and cytokine secretion, and enhanced tumor necrosis factor-α (TNF-α)-induced responses [28] . Even a recent study on biopsy samples of patients with ulcerative colitis treated with an oral anthocyanin-rich bilberry preparation during an open label clinical trial revealed reduced amounts of the proinflammatory cytokines IFN-γ and TNF-α [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EGCG induces apoptosis and suppresses pancreatic cancer cell growth, metastasis by suppressing STAT3 transcription and activation [ 66 ]. In human THP-1 monocytic cells, the inhibition by anthocyanins of IFNγ-activated STAT3 decreases IL-6, tumor necrosis factor α (TNFα), and intercellular adhesion molecule 1 (ICAM-1) secretion [ 67 ]. Targeting to β-catenin and STAT3α is thus an effective approach against metastasis in human colon, prostate, and breast cancer cells [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the control trial reveals no significant reduction in TNF-α level between the treatment and placebo at the end of the study (week-24). Another study also indicates that treatment of human monocytic THP-1 cells with 10 mg/ml anthocyanin-containing bilberry extract (25% anthocyanin content) significantly lowered IFN-γ-induced (100 ng/ml) expressions of MCP-1, IL-6, TNF-α, intercellular adhesion molecule 1 (ICAM-1), and T-cell-specific T-box transcription factor (T-bet) [159]. …”
Section: Mechanisms Of Action In Disease Preventionmentioning
confidence: 99%